Maxillary Sinus Floor Augmentation: a Review of Selected Treatment Modalities - Thomas Starch-Jensen; Janek Dalsgaard Jensen (eJournal of Oral Maxillofacial Research, 2017)
Objectives: The objective of the present study is to present the current best evidence for enhancement of the vertical alveolar bone height and oral rehabilitation of the atrophic posterior maxilla with dental implants and propose some evidence-based treatment guidelines.